The Revolution of Online Business Financial Performance : Before, During and After Pandemic - Amalia Siti Khodijah; Retno Dyah Pekerti (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This study aims to investigate the financial performance of online businesses during the periods before, during, and after COVID-19. A qualitative descriptive analysis was conducted through in-depth interviews with online business practitioners in five cities/regencies in Indonesia. Data analysis was performed using selective coding patterns. The findings indicate that the financial performance of online business organizations experienced a significant improvement during COVID-19. This improvement was supported by several factors, including changes in consumer behavior, operational activities that were acknowledged to be more efficient, the quality of human resources within the organization, and organizational commitment to IT development. Online businesses must adapt quickly to environmental changes and the rapid advancement of IT. Business closures during COVID-19 were found to negatively impact financial performance. This study provides valuable insights into the financial conditions of online businesses during COVID-19, which contrast sharply with those of other business organizations, particularly during the pandemic. The findings offer lessons for business practitioners on managing operational activities affected by the pandemic and formulating anticipatory measures should similar events occur in the future. Policymakers can also consider implementing policies that enable business organizations to maintain their operations even during crises.